Phytochemical Analysis, and in Vitro Evaluation of a Hair Serum Based on Rosmarinus Officinalis Leaves and Coconut Oil - Yadav, Mr. Aditya; Srivastava, Mr. Saurabh (American Journal of Biomedicine and Pharmacy, 2026)
The study aimed to formulate and evaluate a natural hair serum using rosemary (Rosmarinus officinalis) leaves and coconut oil (Cocos nucifera) as a base, with the goal of providing a safe, effective, and natural solution for hair loss and damage, thus serving as an alternative to products with potential chemical side effects. Various formulations with different ingredient concentrations were developed and subjected to a range of evaluations, including organoleptic (appearance, odor, texture), physicochemical (pH, viscosity, homogeneity, stability), and in vitro/in vivo biological assessments. Efficacy was measured using parameters like hair growth rate, thickness, density, hair length, and reduction in hair fall, often compared against a control group using plain coconut oil or standard minoxidil 2% solution.